Measures to Improve the Soil Quality: An Empirical Study of Farmers Opinion in India - SRIVASTAV, SHASHANK (International Journal of Psychosocial Rehabilitation, 2024)
A significant factor in determining the sustainability and productivity of agriculture is soil quality. In India, where agriculture is the primary occupation of a large section of the population, the quality of soil directly impacts the livelihoods of millions of farmers. Despite its significance, soil degradation is a major problem in India, and poor soil quality is the main obstacle to growing crops that produce higher yields and better quality. Soil quality improvement strategies must be developed and put into action. This study investigates Indian farmers' knowledge and perception of soil quality, the causes of soil degradation, and the actions that farmers can take to improve soil health to ascertain the farmers' thoughts on the best ways to improve soil quality. For the creation of focused plans for soil conservation and restoration by policymakers, extension agents, and agricultural practitioners. A sample of 196 farmers was surveyed to know the measures taken by the farmers to improve the soil quality. The researcher also studied the impact of different measures in improving the soil quality and concluded that there is a significant impact of different measures in improving the soil quality.